A PUBLIC PRIVATE PARTNERSHIP NAMBO REGIONAL WASTE IN WEST JAVA: A SYSTEMATIC LITERATURE REVIEW - Senaen, Windriyani Maharani; Musleh, Moh; Tamrin, M. Husni; Subianto, Agus (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2025)
The issue of waste generation is inextricably linked to community life, particularly in densely populated areas where the volume of waste produced significantly impacts the environment and public health. This research examines the challenges of waste management in high-density regions, focusing on the province of West Java, Indonesia, which has seen a substantial increase in waste production due to population growth and changing consumption habits. The study underscores the necessity for effective waste management strategies in accordance with the Waste Management Law No. 18 of 2008, highlighting the role of regional governments in coordinating and supervising waste management efforts. The establishment of the Nambo Regional Waste Processing and Final Disposal Site (TPPAS) is presented as a critical initiative leveraging a Public Private Partnership (PPP) model to achieve sustainable waste management solutions. Through literature review and analysis of relevant regulations and data, the research outlines the operational framework of TPPAS, its capacity to handle significant waste volumes, and the collaborative efforts between public and private sectors to innovate waste processing technologies. The findings reveal both progress and challenges within the TPPAS project, including issues related to financial closure and operational readiness, emphasizing the need for continuous evaluation and adaptation of partnerships to enhance waste management efficiency. Keyword: Public Private Partnership, Waste Management, TPPAS Nambo